Heidegger Pál apostol olvasata - Csaba TÓDOR (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Heidegger’s Reading of Apostle Paul. From 1915 to 1923, Heidegger taught in Freiburg. This was a delicate biographical and important philosophical phase for Heidegger, in which it became increasingly urgent to distance himself definitively from Husserl’s phenomenology. His attempt had developed into a theoretical orientation focused exclusively on the process of eidetic categorization of experience. The subject of his lectures in the academic year 1920/1921 was religion. In these lectures, he (also) dealt with the letters of Paul, which – until then – had been studied mostly by theologians. For this reason, Heidegger’s reading of Paul must be understood as a counterpoint against the background of the theology of the early twentieth century. Thus, Heidegger’s approach to Paul’s letters is primarily phenomenological. At the centre of his interest, there is the (re)discovery and analysis of the concept of eschatology. When Heidegger’s interpretation of eschatology is confronted with the history of eschatology, the true novelty of his approach emerges.